Watching Marginal Bodies: Representation of the Transgender Identity on Turkish Media - Demir, Sertac Timur (European Scientific Journal, ESJ, 2017)
The world in which we live is seen, on the one hand as a global village in some sense and, on the other, as a divided geography. In other words, it is localized and ghettoized simultaneously. The everyday life that transforms rapidly and in an amorphous notion bears testimony to the rise of new identities and belongings as well as new opposition and disengagement. This dilemma generates new and different notion of tension and conflict. Body and gender are considerably significant paradigms in terms of showing and representing this sense of physical, mental and ideological separation; so much so that they change continuously in the shade of freedom and security deadlock. As for media, they do not merely capture but formalized the social events and collective facts. They manipulate the viewer perception and attitudes. From institutional and traditional to individual, digitalized and social media, they redefine the meaning of distant and ambivalent identities and design some clichÃ©s about them. That is why this paper is an attempt to describe the representation of marginal identities in Turkish media mainly through television channels, newspapers, internet and films that may stimulate the controversial relationship between normals and deviant and between insider and outsider. For this purpose, in this study, it is focused on the question of how Turkish media display and represent the transvestites.